Inflammation is Associated with Vascular Remodeling - Repairing Balances in Hypertensive Obese Subjects - Lies Gantini; Syakib Bakri; Andi Wijaya; Anwar Santoso (The Prodia Education and Research Institute (PERI), 2011)
BACKGROUND: Hypertension and obesity are proinflammatory conditions. Vascular remodeling is one of the pathomechanisms reflecting increased cardiovascular (CV) risks and represented as ratio of MMP-9 and sVEGFR-2 concentration. There is no association confirmed between inflammation and remodeling yet. This study was conducted to investigate the correlation between inflammation and vascular remodeling-repairing balances in hypertensive obese subjects.METHODS: This was a cross–sectional study recruited 34 hypertensive obese subjects and 10 hypertensive non obese subjects. They had no antihypertensive medications, neither diabetics nor renal disease and nor acute inflammation detected. Inflammation was assessed as increased hsCRP concentration. Vascular remodeling and repairing were consecutively represented by ratio of MMP-9 and sVEGFR-2.RESULTS: Concentration of hsCRP and MMP-9 were significantly higher in hypertensive obese group than non obese group (2.094±1.90 vs. 0.714±0.40 mg/L; p=0.029; 363.43±143.64 vs. 261.15±61.13 ng/mL, p=0.035, respectively), nonetheless no significant differences of sVEGFR-2 concentration (9.77±2.30 vs. 9.76±1.38 pg/mL, p=0.980) found in both groups. Ratio of MMP-9/sVEGFR-2 was significantly higher in hypertensive obese group than those in non-obese group (38.67±16 vs. 27.22±10, p=0.038). Likewise, they had more subjects with ratio of MMP-9/sVEGFR-2 ≥31.53. This figure is considered as cut-off point of vascular remodeling versus repairing.CONCLUSION: In hypertensive obese subjects, inflammation was activated and vascular remodeling more dominant than repairing process. Inflammation was associated with increased remodeling-repairing balances.KEYWORDS: Matrix Metalloproteinase-9 (MMP-9), soluble Vascular Endothelial Growth Factor Receptor-2 (sVEGFR-2), high sensitivity C-Reactive Protein (hsCRP).